2005
DOI: 10.1080/00016470510030805
|View full text |Cite
|
Sign up to set email alerts
|

Poor predictive value of broad-range PCR for the detection of arthroplasty infection in 92 cases

Abstract: The PCR technique cannot be recommended for the routine detection of prosthetic infection. The large number of false positive results may represent sample contamination, or bacterial presence related to low-virulence organisms, low bacterial load, or a strong host immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(100 citation statements)
references
References 36 publications
3
93
1
3
Order By: Relevance
“…16S rRNA gene real-time PCR results were in line with the conventional culture results in about 96 % of the studied patient cases. These findings seem to be consistent with previously published data on NAAT techniques, indicating a relatively wide range of sensitivity and specificity [8][9][10][11][12]. NAATs may reasonably expand the diagnostic panel and contribute to a higher recovery rate especially after antimicrobial use.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…16S rRNA gene real-time PCR results were in line with the conventional culture results in about 96 % of the studied patient cases. These findings seem to be consistent with previously published data on NAAT techniques, indicating a relatively wide range of sensitivity and specificity [8][9][10][11][12]. NAATs may reasonably expand the diagnostic panel and contribute to a higher recovery rate especially after antimicrobial use.…”
Section: Discussionsupporting
confidence: 91%
“…Only few studies have assessed the diagnostic utility of nucleic acid amplification test (NAAT) techniques in this context. The reported findings for different PJI-associated materials indicate a wide range of sensitivity (50-92 %) and specificity (65-94 %) [8][9][10][11][12][13]. Results from a recent study comparing 16S rRNA gene PCR and consecutive sequencing of sonication fluid with culture of synovial aspirates, tissue samples and sonication fluids reports that 16S rRNA gene PCR improved sensitivity [14].…”
Section: Introductionmentioning
confidence: 99%
“…Insofern stellt sich die Frage, inwieweit es sich bei positiven Keimnachweisen in nur einem Diagnostikverfahren um "echte" Befunde oder um Kontamination handelt bzw. ob insbesondere bei dem Verfahren der PCR nicht eine "oversensitivity" zu beachten ist [17,18]. Diese Frage ist bisher nicht abschließend geklärt.…”
Section: Bedeutung Für Die Praxis?unclassified
“…However, the expense and diagnostic value of PCR in comparison to bacterial culture [2][3][4] warrant the use of this molecular method only selectively and not routinely, and in addition to bacterial culture. In our center, PCR has been performed in fewer than 10% of all revision arthroplasties (i.e.…”
Section: Characteristicmentioning
confidence: 99%
“…Several drawbacks need to be considered when using this technique, including the lack of susceptibility results (except for methicillin-resistant Staphylococcus aureus) and problems in identifying a mixture of bacterial species in a single specimen [1]. A number of studies have indicated that the routine use of PCR in PJIs does not offer a diagnostic advantage over bacterial culture [2][3][4]. However, this molecular method can detect bacterial DNA in samples when conventional cultures are negative due to previous antimicrobial exposure or unfavorable growth conditions.…”
mentioning
confidence: 99%